(untitled) (Journal of Engineering, 2015)
As asphalt concrete wearing course (ACWC) is the top layer in the pavement structure, the material should be able to sustain stresses caused by direct traffic loading. The objective of this study is to evaluate the influence of aggregate gradation and mineral filler type on Marshall Properties. A detailed laboratory study is carried out by preparing asphalt mixtures specimens using locally available materials including asphalt binder (40-50) penetration grade, two types of aggregate gradation representing SCRB and ROAD NOTE 31 specifications and two types of mineral filler including limestone dust and coal fly ash. Four types of mixtures were prepared and tested. The first type included SCRB specification and limestone dust, the second type included SCRB specification and coal fly ash, the third types included ROAD NOTE 31 specification and limestone dust and the fourth type included ROAD NOTE 31 specification and coal fly ash. The optimum asphalt content of each type of mixtures was determined using Marshall Method of mix design. 60 specimen were prepared and tested with dimension of 10.16 cm in diameter and 6.35 cm in height. Results of this study indicated that aggregate gradation and filler type have a significant effect on optimum asphalt content and Marshall Properties. From the experimental data, it was observed that the value of Marshall Stability is comparatively higher when using fly ash as filler as compared to limestone dust.